INTERNALISASI NILAI KARAKTER DALAM KISAH MUHAMMAD AL-FATIH UNTUK PENDIDIKAN GEN-Z - Setiaji, Heri; Anshori, Irfan; Rofiq, Ahmad; Julianti, Lingga (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
Character education is a demand in national education to build and cultivate good character in students. This research aims to find out the character values in the story of Muhammad Al-Fatih and how to implement the values of character education in the story of Muhammad Al-Fatih in today's education. This research uses qualitative methods which produce descriptive data through two types of approaches, namely library research and field research. Data collection techniques in this research used observation, interview and documentation techniques. Interviews were conducted with students and teaching staff. The results of the research show that there are character education values in Muhammad Al-Fatih that are relevant to the 18 character education values according to the Ministry of National Education. The results of field research at MTs Masyariqul Anwar Caringin show that students' attitudes, manners and behavior are improving. Learning the History of Islamic Culture through the exemplary story method of the character Muhammad Al-Fatih integrates 8 character education values, namely religious, discipline, curiosity, hard work, creativity, independence, democracy and responsibility.